The The Use of Zoom Meeting for Distance Learning in Teaching English to Accounting Students of Politeknik Sawunggalih Aji Kutoarjo - Desi Innanti Wicaya Ningrum (Politeknik Sawunggalih Aji, 2023)
Abstract To avoid the spread of Covid19 government closes all of the education sectors from primary school to university level and suggests the distance learning by utilizing technology connected to the internet. Zoom Meeting is one of the platforms that can be used by educators to teach their students in distance teaching and learning. This application allows learning activities or discussions like in face to face learning. Thus, the lecturer and students can do their teaching and learning activity like in offline teaching and learning activity. The aim of this research is to describe the condition that occur in distance learning process by using Zoom Cloud Meeting. This is descriptive qualitative method with data collection techniques performed by distributing questionnaire via Google Form and doing interview through Zoom Cloud Meeting to dig more information of respondents’ questionnaire answer. The results showed that students gave positive responses that they felt enjoy in learning by using Zoom Meeting. Meanwhile, the students also faced several challenges in using Zoom Meeting during learning which include internet network and consuming much internet quota. However, Zoom Cloud Meeting application is effective to substitute offline meeting in pandemic situation because it enables discussion like in a real classroom.